Виявлення отруйних домішок в етанолі методом поверхневого плазмонного резонансу - Радов, Денис Георгійович; Маслов, Володимир Петрович; Дорожинський, Гліб Вячеславович (НТУ "ХПІ", 2017)
Основною причиною смертності від алкоголю в Україні є присутність в ньому отруйних домішок таких як метанол. Існуючі методи контролю якості етанолу, як основної складової алкоголю, є коштовними та потребують спеціалізованого обладнання високої вартості, допоміжних реагентів та кваліфікованого персоналу. Альтернативним є метод на основі явища поверхневого плазмонного резонансу, котрий дозволяє визначати менші концентрації шкідливих домішок у етанолі (0,00202%об.) за регламентовані стандартом України (0,005%об.). Експериментально показано, що такі концентрації не детектуються методами кондуктометричним та ІЧ-спектрометрії. Результати досліджень можуть бути використані для вдосконалення існуючих та створення нових методик контролю домішок в етанолі.

Every year by low quality alcohol poisoning in Ukraine 10 thousand citizens died, and in 2017 the projected number of deaths can grow significantly. The main cause poisoning and death are in the presence of alcoholic beverages contaminants, fusel oils, esters, toxic alcohols (eg, methanol, isopropanol, pentanol), aldehydes. To control the quality of ethanol mainly used chromatographic method, which is expensive, require specialized equipment of high value ancillary reagentsand qualified personnel. An alternative method may be based on the phenomenon of surface plasmon resonance (SPR), which allows for rapid analysis (measurement of length less than 10 sec.) And can be less expensive for existing methods. Diagnosing devices that are based on the phenomenon of surface plasmon resonance, have high sensitivity to low concentrations (0.01-2 mg/kg) of liquid and gaseous substances and are characterized by high accuracy measurements allows you to define a smaller concentration of contaminants in ethanol (0.00202% vol.) for the regulated standard of Ukraine (0,005% vol.). Shown experimentally that such concentration is not detected by conductometry and IR spectrometry. The research results can be used to improve existing and create new methods for monitoring toxic contaminants in ethanol.
Detection toxic impurities in ethanol by surface plasmon resonance method
Keywords: метанол; отруйні органічні речовини; ІЧ-спектрометрія; ВОЗ; повне внутрішне відбиття; ППР-рефрактометр; methanol; toxic organic substances; IR spectrometry